Characterization of Two Immunodominant Antigenic Peptides in NSP2 of PRRSV-2 and Generation of a Marker PRRSV Strain Based on the Peptides - Li, Dong-Yan; Cui, Xing-Yang; Huang, Xin-Yi; Hu, Yue; Tian, Xiao-Xiao; Wang, Tao; Yang, Yong-Bo; Wang, Qian; Tian, Zhi-Jun; Cai, Xue-Hui; An, Tong-Qing (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome (PRRS) is a widespread disease with great economic importance in the pig industry. Although vaccines against the PRRS virus (PRRSV) have been employed for more than 20 years, differentiating infected from vaccinated animal remains challenging. In this study, all 907 non-structural protein 2 (NSP2) full-length sequences of PRRSV-2 available from GenBank were aligned. Two peptides, at positions 562–627 (m1B) and 749–813 (m2B) of NSP2, were selected, and their potential for use in differential diagnosis was assessed. Both m1B and m2B were recognized by PRRSV-positive pig serum in peptide-coated enzyme-linked immunosorbent assays. Further epitope identification yielded five overlapping short peptides for the immunodominant regions of m1B and m2B. Using the infectious clone of PRRSV HuN4-F112 as a template, the deletion mutants rHuN4-F112-m1B, rHuN4-F112-m2B, and rHuN4-F112-C5-m1B-m2B were generated and successfully rescued in Marc-145 cells. Growth kinetics revealed that deletion of m1B and m2B did not significantly affect virus replication. Hence, m1B and m2B show potential as molecular markers for developing a PRRSV vaccine.